The cooperative deformation test of an embedded FBG sensor and strain correction curve verification. (1st August 2022) - Liao, Menghui; Liang, Sheng; Luo, Rong; Xiao, Yuxiang
Highlights: The FBG sensor can be maintained at a high level in the nondestructive stage of asphalt pavement. The armored FBG sensor has the best effect on monitoring the internal strain of pavement structure. Temperature has a significant influence on the monitoring accuracy of the FBG sensor. Abstract: In order to accurately measure the internal structural strain of asphalt pavement using a fiber Bragg grating (FBG) sensor, the cooperative deformation characteristics of the FBG sensor and asphalt mixture were investigated. First, the cooperative deformation test and evaluation method were designed for the developed three FBG sensors, and the strain correction curve was drawn to modify the measurement results. Next, the sensitivity, stability, survival rate, and other factors were considered comprehensively to optimize the FBG sensor and make it suitable for the internal monitoring of asphalt roads. Finally, the accuracy of the average strain correction curve was verified. The main conclusions are as follows: (a) the strain data monitored by the embedded FBG sensor can reflect the deformation accumulation and elastic recovery of the material in asphalt roads; (b) the FBG sensors, with large or small correction coefficients, affect the measurement accuracy and stability of long-term monitoring; (c) the strain data fluctuated from 8.1 to 9.05% after temperature compensation; and (d) the average strain correction curve can modify the strain monitored by the FBG sensor. The measurement results are accurate, and the measurement error was about 3.01–9.14%.